Answer: 19x - 8
Steps
-5(3x + 7)
Apply the distributive law: a( b + c ) = ab + ac
a = -5, b = 3x, c = 7
= -5 * 3x + (-5) x 7
Apply minus - plus rules
+(-a) = -a
= -5 * 3x - 5 x 7
Simplify
-5 * 3x - 5 x 7
Multiply the numbers: 5 x 3 = 15
= -15x - 5 x 7
Multiply the numbers: 5 x 7 = 35
= -15x - 35
Plug in the values
-15x - 35 - 4(x - 4) + 11
------------------------------------------------------------------
-4(x - 4)
Apply the distributive law: a( b - c ) = ab - ac
a = -4, b = x, c = 4
= -4x - (-4) * 4
Apply minus - plus rules
-(-a) = a
= -4x + 4 * 4
Multiply the numbers: 4 * 4 = 16
= -4x + 16
Plug in the values
-15x - 35 - 4x + 16 + 11
------------------------------------------------------------------
Simplify
-15x - 35 - 4x + 16 + 11
Group like terms
= -15x - 4x - 35 + 16 + 11
Add similar elements: -15x - 4x = -19x
= -19x - 35 + 16 + 11
Add/Subtract the numbers: -35 + 16 + 11 = -8
= 19x - 8